The case of child abuse and neglect: identification of non-accidental injuries by medical professionals at the emergency and trauma department - Jamaludin, Anne Noor Sri Juwaneeta; Oxley, Jennifer; Kia, Fatt Quek (2018)
It is well established that accidental and non-accidental injuries/child abuse and neglect (CAN) are a major public health problem globally. Not only do they affect individuals, injuries affect families, the community, government and internationally as well. Injuries span throughout childhood and into adulthood. Purpose of this study is to identify what are the difficulties and challenges in identifying and reporting CAN cases at the emergency (ED) department in Malaysian hospitals. Thirty in-depth interviews were conducted at the ED in three major hospitals in the Klang Valley, Malaysia which consists of specialists, medical officers, nurses and medical assistants. The study found that there is a significant gap identified in medical professionals’ knowledge and skills related to understanding, identifying and detecting CAN, particularly among medical officers who are in charge of diagnosis and reports in the hospital. Those who had previous experience or encounters in dealing with CAN cases would have higher suspicion index compared to those who haven’t. Other medical professionals such as nurses and medical assistants although do not have the mandate to diagnose or report of CAN cases, needed to have the basic knowledge and awareness and play more active role in their respective settings.